APLIKASI ABSENSI MENGGUNAKAN QR CODE - rizky fauzy; Husni Lubis; Fachrul Rozi Lubis (Jurnal Media Informatika, 2022)
In general, the student learning process will be absent every day with the aim of knowing whetherthe student can find out whether the student can follow the learning process. Land problemscurrently still use the manual way of doing attendance which will then encounter several obstaclesincluding easily damaged such as attendance data that is often lost, the difficulty in finding studentattendance data and the slow time in processing student attendance data, it is considered that thereare still many information systems that have not been implemented. one of them is an attendanceinformation system for students. To overcome this problem, an attendance application will bedesigned that utilizes QR code technology that handles the student attendance process, so that itcan assist in searching for data and information. This study was built using the php programminglanguage and mysql database, the purpose of this research is to produce student attendanceapplications using website-based QR code technology and make attendance processing effective